Analysis of Information Utilization of Budget Realization on Performance in Regional Goverment - Silfin Nabila (Perkumpulan Praktisi Akuntansi Indonesia, 2022)
The budget realization report provides benefits for decisions that will later be accounted for. In government agencies, the performance of users of reports is very important to understand the information on budget realization reports. Where the budget realization report provides information on an overview of the sources, allocations, and use of economic resources managed by the government. This budget realization report is prepared to provide relevant information on the financial position and all transactions carried out by an entity during one period, hereby the performance of the report users must understand the benefits of the budget realization report itself. This study aims to specifically analyze the effect of user performance characteristics on the utilization of budget realization report information. Data were collected from distributing questionnaires to students to understand the performance that should be done in government. Statistical testing was performed using regression analysis using the SPSS 23.0 statistical tool.